Acceleration of near‐surface strong winds in a dry, idealised extratropical cyclone. (21st August 2014) - Slater, Tim P.; Schultz, David M.; Vaughan, Geraint
<x xml:space="preserve">Abstract</x> To understand near‐surface strong winds in extratropical cyclones, a simulation of a dry, idealised baroclinic wave is presented. The forces that accelerate the winds are analysed using the terms in the horizontal momentum equation. Two regions of strong near‐surface winds developed within the simulation: one to the east of the low centre and the other to the southwest. The flow to the east, resembling the cold conveyor belt, accelerated as it passed through the strong pressure gradient associated with the warm‐frontal zone. This acceleration was reduced by friction near the surface. The winds to the southwest were characterised by three airstreams. One airstream consisted of air parcels that started north of the warm front near the surface, accelerated north of the warm front, encircled the low and continued to accelerate to the southwest of the low. The increases in wind speed in this airstream (also part of the cold conveyor belt) resulted from the along‐flow pressure gradient force being greater than friction. The second airstream consisted of air parcels that descended west of the cold front and maintained their speed during descent until they were slowed either by friction in the boundary layer, or as they moved southward against the local pressure gradient. Between these two airstreams, a third airstream was characterised by air parcels that accelerated during descent from the mid to lower troposphere whilst moving around the bent‐back front. This airstream bears some resemblance to the sting jet and was accelerated by the pressure gradient force on descent until it encountered increased friction or moved against the local pressure gradient.